Secure communication between lightweight computing devices over the Internet - Jenkin, M.; Dymond, P. (35th Annual Hawaii International Conference on System Sciences (HICSS-35 2002), 2002)
The advent of light, low-power handheld computer devices such as Windows CE, Palm/sup TM/ and Handspring, is changing the way in which mobile users interact with their home office. These devices can be connected to the Internet through both physical and wireless connections, and sensitive data transferred to and from these devices are subject to interception by a third party. Real-time encryption/decryption of data in handheld computers is complicated by the limited computing power available in these devices. In this paper we describe a method for secure transmission of data between remote handheld devices and other users (including other handheld devices) on the Internet. The system relies on one-time-pad technology which is ideally suited for handheld computing. The process of encrypting/decrypting data requires very little computation, and the generation of the random pads can be accomplished outside of the handheld devices. A prototype system is described which permits secure transmission of data through IR, radio Ethernet, or physical connection.